Analysis of the Influence of E-Wom on Repurchase Intention: the Mediating Role of Customer Loyalty and Satisfaction - Nasrulloh, Rifqi Syarif; Rohim , Annisa Nur; Idries, Fahmy Akbar (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this study is to investigate the impact of electronic word-of-mouth (e-WOM) on repurchase intentions for products from Mbah Blangkon Yogyakarta MSME. The study aims to explore the roles of customer loyalty and satisfaction as mediating variables in this relationship. Additionally, it seeks to apply the AISAS (Attention, Interest, Search, Action, and Share) framework to better understand how e-WOM influences consumer decision-making processes. Methodology: The research approach used was quantitative, with purposeful sampling procedures. Data were acquired through surveys from Mbah Blangkon Yogyakarta consumers who had made more than five transactions in the previous three months, offered good feedback, and evaluated the products highly. Data was analyzed using SEM-PLS, with a total of 110 respondents. Results: The study reveals that e-WOM has a positive and significant impact on repurchase intentions, both directly and mediated by customer loyalty and satisfaction. Specifically, the quality of e-WOM enhances repurchase intentions, whereas the quantity of e-WOM negatively affects them. Conclusions: Electronic word of mouth has a good and significant impact on repeat sales because customer reviews provide useful information about the product. In the context of this study, customer loyalty and satisfaction serve as a median for recurrent purchases, which are positive and significant. Another finding from this study is that loyalty has a significant impact on repeat sales since consumers are willing to go to further lengths to obtain the goods. Limitations: This study has several limitations: it focuses on a single MSME in Yogyakarta, which may limit generalizability. Additionally, it relies on self-reported data. Finally, the research examines only specific variables related to e-WOM. Contribution: Managerial implications indicate that Mbah Blangkon MSME can use e-WOM as an effective marketing technique to increase repurchase intentions through customer loyalty and satisfaction. The AISAS model can help in designing targeted digital marketing efforts. This research provides valuable insights for business practitioners in leveraging e-WOM to enhance customer relationships.